Labor Issues in Infrastructure Reform : A Toolkit, Module 1 - Public-Private Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
A universal concern in infrastructure reforms is the effect such reforms have on labor. State-owned infrastructure firms often employ more people than required for efficiency, and often under favorable terms and conditions of service, leading to lower labor productivity and higher labor costs than private employers would bear. Some reform, in particular those involving private participation in infrastructure (PPI), may thus prompt surplus labor and changes in working conditions as governments adjust the work force to prepare for PPI, or as new owners or operators introduce efficiency improvements and expose enterprises to greater management discipline, new technologies, and increasing competition. The primary objective of this Toolkit is to provide practical tools and information to help policymakers handle labor issues in private participation in infrastructure (PPI). The Toolkit consists of seven modules: 1) Framework and overview of the entire toolkit; 2) Labor impacts of PPI; 3) Assessing the size and scope of labor restructuring; 4) Strategies and options; 5) Key elements of a labor program; 6) Engaging with stakeholders; 7) Monitoring and evaluation of labor programs. The Toolkit also contains a web-based CD-ROM with searchable documents, spreadsheets, sample terms of reference for obtaining the needed expertise to carry out various labor-related tasks, case studies, and other relevant data.